2022
DOI: 10.2298/psi210204014a
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of psychological well-being in the relationship between the psychological contract and professional engagement

Abstract: This study was conducted using structural equation modelling to examine the relationship between the psychological contract, psychological well-being, and professional engagement. The sample of the study included 416 teachers who were selected using a disproportionate cluster sampling method from primary and middle schools in Turkey. In analysing relations between variables, mediation testing was performed using the structural equation model and the bootstrap method. The results of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Since accepting underreporting of audit time is a dysfunctional work behaviors, therefore, our study resonate with various studies that conclude that work engagement is a positive work motivation (Bouckenooghe et al 2022) that increases dedication, vigor, and absorption of employees with their jobs. Highly engaged employees become engrossed with their work (Alev, 2022). They understand, implement and master novel cognitive skills to accomplish the assigned tasks (Koch et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since accepting underreporting of audit time is a dysfunctional work behaviors, therefore, our study resonate with various studies that conclude that work engagement is a positive work motivation (Bouckenooghe et al 2022) that increases dedication, vigor, and absorption of employees with their jobs. Highly engaged employees become engrossed with their work (Alev, 2022). They understand, implement and master novel cognitive skills to accomplish the assigned tasks (Koch et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The research findings support it; many studies compared the levels of stress teachers go through affect their mental health. Other working people in different occupations have shown more mental stress in the teachers, level of stress, mental distress, and burnout [ 65 ]. It is a globally agreed-upon phenomenon that work-related demands and stress on the academic’s part have increased, and the trend is projected to intensify in the future [ 37 ].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Several studies demonstrated that environmental mastery has a significant and positive influence on organizational values, and alignment of personal values as a mediator [ 71 , 72 , 73 ], and the psychological well-being of universities teachers [ 74 , 75 , 76 , 77 ]. Similarly, personal growth is also mediated between spiritual orientation and psychological well-being [ 65 , 66 , 67 ]. The following hypotheses are framed based on previous literature:…”
Section: Review Of Literaturementioning
confidence: 99%
“…Teachers who are dedicated to their profession will have high enthusiasm and emotional attachment to their work. Many researchers are in the field of education research related to professional engagement (Alev, 2022;Dilekçi & Limon, 2020;Kozikoglu & Senemoglu, 2021;Kozikoğlu & Senemoğlu, 2019). Based on a study conducted by Watt et al (2014) explains that the professional engagement of teachers is formed based on their experience during their teacher education.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers who are professionally engaged must have professional competence and commitment to their work to realize quality learning for students (Shukla, 2014). Several studies have also shown a significant relationship between teacher professional engagement and student achievement (Alev, 2022;Butucha, 2013;Cansoy et al, 2022;Dilekçi & Limon, 2020;Mojavezi & Tamiz, 2012;Shukla, 2014).…”
Section: Introductionmentioning
confidence: 99%